KOMUNITAS AVIFAUNA DI SEPANJANG ALIRAN ANAK SUNGAI WAILAWA DESA TAWIRI KECAMATAN TELUK AMBON, KOTA AMBON - Andri Tuhumury (Jurnal Hutan Tropis, 2018)
The study was conducted in April 2017, located along the Wailawa watercourses, Tawiri Village, Ambon. The method applied in these studies were Point Count, while data analysis using Shannon-Wiener Diversity Index, Evenness Index, Domination Index, Similarity Index, and Guild Composition. The results showed that the number of bird species found along Wailawa watercourse were 28 species of 25 genera, 17 families, and 8 orders. The diversity of bird species is moderate (H ‘= 2,54). The bird species similarity analysis resulted in three bird communities, including: (1) bird communities in mangrove forest, estuaries with grass vegetation, (2) bird communities in garden and settlement habitats, and (3) bird communities in mixed forest habitat. Mangrove forest and estuaries have the highest species similarities (0,63). Estuaries and mix gardens have the lowest bird similarities (0,05). Bird communities in mangrove forests and estuaries are heterogeneous because they have more species with a more equitable distribution of species abundance, while in other habitat, their are homogenous because of relatively have a low species diversity with uneven distribution of species abundance.Penelitian ini bertujuan menganalisis komunitas burung, meliputi kekayaan jenis, keanekaragaman jenis, kelimpahan relatif, kemerataan jenis, foraging guild, serta kesamaan jenis. Penelitian dilakukan pada bulan April 2017, berlokasi di sepanjang Anak Sungai Wailawa, Desa Tawiri, Kota Ambon. Metode pengambilan data adalah metode point count, sedangkan analisis data menggunakan Indeks Keanekaragaman Shannon-Wiener, Indeks Kemerataan Jenis Evennes, Indeks Dominasi Jenis, Indeks Kesamaan Jenis, dan Foraging guild. Hasil penelitian menunjukkan jumlah jenis burung yang ditemukan sebanyak 28 jenis dari 25 genus, 17 famili, dan 8 ordo. Keanekaragaman jenis burung tergolong sedang (H’ = 2,54). Hasil analisis tingkat kesamaan komunitas menghasilkan tiga komunitas burung, meliputi : (1) komunitas burung di hutan mangrove-muara sungai bervegetasi rumput, (2) komunitas burung di kebun dan permukiman, serta (3) komunitas burung di kebun campur. Hutan mangrove dan muara sungai memiliki kesamaan jenis burung tertinggi, yakni 0,63. Muara sungai dan kebun campur memiliki kesamaan jenis burung terendah, yakni 0,05. Komunitas burung di hutan mangrove dan muara sungai adalah komunitas heterogen karena memiliki lebih banyak spesies dengan distribusi kelimpahan spesies yang lebih merata, sedangkan komunitas burung pada tipe habitat lainnya adalah komunitas homogen karena keragaman jenis relatif rendah dan distribusi kelimpahan spesies tidak merata.